Characterization of the diagnostic properties of general practice physicians from Servicio de Salud Araucanía Sur for the radiological diagnosis of community-acquired pneumonia - Godoy, Marcelo; De Grazia, José A.; Otárola, Ávaro; Serón, Pamela (Revista Chilena de Salud Pública, 2013)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Objectives: To characterize the diagnostic properties of a group of general practice physicians (GPPs) from Servicio de Salud Araucanía Sur for the radiological diagnosis of communityacquired pneumonia (CAP). Method: 201 adult patients from Gorbea Hospital were selected according to the presence of clinical signs compatible with CAP. We evaluated the sensitivity, specificity and predictive values of the interpretation of chest radiographs for the diagnosis of CAP, obtained from the consensus of 5 GPPs, compared with the radiographic interpretation of a radiologist (gold standard). Results: The evaluation of radiographs by GPPs reported 89 cases with diagnostic of CAP (44%) and the assessment by radiologist reported 51 (25%). The Kappa value found was 0.46 [0.34-0.57], which means a moderate agreement level. The sensitivity of GPPs for radiological diagnosis of CAP was 86.5% [74-94], specificity was 70.4% [62-77]. The positive predictive value was 50.6% [39-61] and the negative predictive value was 93.7% [87-97]. Conclusions: GPPs have a good sensitivity for radiological diagnosis of CAP, with a lower specificity, determining a high number of false positives. The main utility of chest radiograph used by GPPs for CAP diagnosis remains in its high capacity to detect negative cases, but it fails in 50% of the cases asserting to view a consolidation. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>